Integration of Flowering Signals in Winter-Annual Arabidopsis - Michaels, Scott D. (American Society of Plant Biologists, 2005)
Photoperiod is the primary environmental factor affecting flowering time in rapid-cycling accessions of Arabidopsis (Arabidopsis thaliana). Winter-annual Arabidopsis, in contrast, have both a photoperiod and a vernalization requirement for rapid flowering. In winter annuals, high levels of the floral inhibitor FLC (FLOWERING LOCUS C) suppress flowering prior to vernalization. FLC acts to delay flowering, in part, by suppressing expression of the floral promoter SOC1 (SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1). Vernalization leads to a permanent epigenetic suppression of FLC. To investigate how winter-annual accessions integrate signals from the photoperiod and vernalization pathways, we have examined activation-tagged alleles of FT and the FT homolog, TSF (TWIN SISTER OF FT), in a winter-annual background. Activation of FT or TSF strongly suppresses the FLC-mediated late-flowering phenotype of winter annuals; however, FT and TSF overexpression does not affect FLC mRNA levels. Rather, FT and TSF bypass the block to flowering created by FLC by activating SOC1 expression. We have also found that FLC acts as a dosage-dependent inhibitor of FT expression. Thus, the integration of flowering signals from the photoperiod and vernalization pathways occurs, at least in part, through the regulation of FT, TSF, and SOC1.